2013
DOI: 10.15204/jkobgy.2013.26.4.030
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-depressive Effect of Samul-tanggahyangbuja on Chronic Mild Stress in Ovariectomized Rats

Abstract: Objectives: The purpose of the present study is to investigate anti-depressive effects of Samul-tanggahyangbuja (SGH) on ovariectomized and chronic mild stress (CMS) induced rats. Methods: Ovariectomized rats were exposed to CMS for 4 weeks. Changes of depression behavior were tested by using sucrose intake test (SIT), elevated plus maze (EPM), forced swimming test (FST) and Morris water maze test (MWMT) in rats until being orally medicated with SGH (100 or 400 mg/kg/day). In addition, the serum levels of cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…A study evaluating the effectiveness of an herbal-based obesity management program on an obese PCOS patient concluded that Changbudodam-tang (Cangfu Daotan-tang) is effective in treating oligomenorrhea associated with obesity in PCOS [20]. Additionally, herbal prescriptions such as Chokyung-san (Tiaojing-san), Changbudodamtang (Cangfu Daotan-tang), Onkyung-tang (Wenjingtang), Gyejibokryeong-hwan (Guizhi Fuling-wan), and Chokyungjongok-tang (Tiaojing Zhongyu-tang) were found to alleviate ovulatory dysfunction and apoptosis of granulosa cells, normalize the endometrium, and improve acne vulgaris, oligomenorrhea and excess androgen-related conditions associated with female ovarian dysfunction [21][22][23]. Several studies using animal PCOS models also tested the effectiveness of major herbal medicine prescriptions, such as Chokyung-san (Tiaojing-san), Gamiguibi-tang (Jiawei Guipi-tang), and Changbudodam-tang (Cangfu Daotan-tang) [23][24][25][26][27], and presented favorable results.…”
Section: Potential Mechanism and Implication For Researchmentioning
confidence: 99%
“…A study evaluating the effectiveness of an herbal-based obesity management program on an obese PCOS patient concluded that Changbudodam-tang (Cangfu Daotan-tang) is effective in treating oligomenorrhea associated with obesity in PCOS [20]. Additionally, herbal prescriptions such as Chokyung-san (Tiaojing-san), Changbudodamtang (Cangfu Daotan-tang), Onkyung-tang (Wenjingtang), Gyejibokryeong-hwan (Guizhi Fuling-wan), and Chokyungjongok-tang (Tiaojing Zhongyu-tang) were found to alleviate ovulatory dysfunction and apoptosis of granulosa cells, normalize the endometrium, and improve acne vulgaris, oligomenorrhea and excess androgen-related conditions associated with female ovarian dysfunction [21][22][23]. Several studies using animal PCOS models also tested the effectiveness of major herbal medicine prescriptions, such as Chokyung-san (Tiaojing-san), Gamiguibi-tang (Jiawei Guipi-tang), and Changbudodam-tang (Cangfu Daotan-tang) [23][24][25][26][27], and presented favorable results.…”
Section: Potential Mechanism and Implication For Researchmentioning
confidence: 99%
“…모델 흰쥐에 대하여 四物湯加香附子의 항우울 효과 9) , 加 減酸棗仁湯의 항스트레스 효과 10) , 하엽추출물의 항우울 효과 11) 등이 있고, 白茯笭藥鍼에 대한 실험적 연구로 문 등이 정상 흰쥐의 五臟兪穴에 白茯笭藥鍼을 투여하여 腎 臟機能에 유의한 효과를 얻은 실험 12) , Kim et al이 흰쥐 의 陰谷穴에 白茯笭藥鍼을 투여하여 Lipopolysaccharide 로 유발된 신기능 손상에 유효한 효과 13…”
Section: 만성 스트레스에 대한 실험적 연구로 만성 스트레스unclassified
“…足三里와 三陰交는 寧心健脾, 鎭靜安神하는 효능이 있어 서 정신신경계 질환에 다빈도 처방이다 36) . 지금까지의 스트레스에 대한 연구는 실험방법이 약물 의 경구투여 방식 [9][10][11]…”
Section: Serum Aminotransferase에 미치는 영향unclassified